Redesain User Interface Website Rental Mobil BSM Trans Menggunakan Metode User Centered Design Untuk Meningkatkan Retensi Pelanggan - Wardhana, I Wayan Frico Ari; Haq, Endi Sailul; Ratri, Arum Andary (Jurnal Informatika dan Komputer, 2024)
BSM Trans is a company engaged in car rental ranging from car rental services plus drivers, Off Key Car Rental, All In or Carter Package Car Rental, Tour and Travel Services, Airport Shuttle and Expedition Services both small and large scale. The purpose of this research is to increase customer retention and improve the design of the BSM Trans website using the User Centered Design (UCD) approach. The research method uses User Centered Design (UCD) in redesigning the BSM Trans website. After that, it was continued with the System Usability Scale (SUS) method to involve the use of questionnaires distributed through google forms by applying the SUS questionnaire to test the usability of a system. The results obtained are research before the SUS redesign that was obtained 38% where the grade scale was at F with poor indicators. But after redesigning the SUS value obtained increased dramatically by 84.75% which is on grade scale A with good indicators. This proves that the design improvements made bring an increase in the average SUS score by 46.75% This proves that testing with SUS in this study was successfully carried out and the new design design can be well received by users.